Recall, appeal and willingness to try cigarettes with flavour capsules: assessing the impact of a tobacco product innovation among early adolescents - Abad-Vivero, Erika N (Tob Control, 2016)
BACKGROUND: Use of flavour capsule varieties (FCVs) of cigarettes has rapidly increased in many countries. Adolescents are attracted to flavours; yet, surprisingly, no quantitative study has explored adolescents' perceptions of these products. OBJECTIVE: To characterise the appeal of FCVs for young adolescents in Mexico. METHODS: In 2015, surveys were conducted with a representative sample of Mexican middle school students (n=10 124; ages 11–16 years; mean 12.4 years). Students viewed and rated packs for FCVs and non-FCVs from major brands (Marlboro, Camel, Pall Mall), with brand names removed. For each pack, students were asked to write the brand name (ie, brand recall), to evaluate pack attractiveness, and to indicate the pack they were most interested in trying (including a ‘none’ option). Logistic generalised estimating equation (GEE) models regressed brand recall, pack attractiveness and interest in trying on brand and FCV (yes vs no), controlling for sociodemographics and smoking risk factors. RESULTS: Marlboro regular, Camel regular, Camel light and Pall Mall FCVs were most often recalled (25%, 17%, 9%, 8%). Packs for Pall Mall FCVs and Camel FCVs were most often rated as very attractive (13%, 9%, respectively) and of interest for trial (22%, 13%) along with Marlboro regular (14%). In GEE models, FCVs were independently associated with greater attractiveness (adjusted OR (AOR)=1.83, 95% CI 1.72 to 1.94) and interest in trying (AOR=1.74, 95% CI 1.54 to 1.96). Perceived pack attractiveness was also independently associated with greater interest in trying (AOR=5.63, 95% CI 4.74 to 6.68). CONCLUSIONS: FCVs appear to be generating even greater appeal among young adolescents than established non-FCVs in dominant brand families.